Prevalence of cardiovascular risk factors among elderly Brazilians over eighty with ischemic stroke Prevalência de fatores de risco cardiovasculares em idosos brasileiros acima de 80 anos e com acidente cerebrovascular isquêmico - Alexandre Pieri; Mariana Spitz; Tania Oliveira Lopes; Claudia Garcia de Barros; Marcelo Wood Faulhaber; Alberto Alain Gabbai; Miguel Cendoroglo-Neto (Arquivos de Neuro-Psiquiatria, 2008)
INTRODUCTION: An ischemic stroke is usually a catastrophic event, mostly in the elderly. Cardiovascular involvement is the leading cause of ischemic stroke in this age population and hence the knowledge about its risk factors is important for the definition of specific policies of prevention. PURPOSE: To evaluate the prevalence of cardiovascular risk factors in patients with age equal to or above 80 in a hospital population with ischemic stroke. METHOD: Retrospective study of consecutive patients diagnosed with ischemic stroke admitted to a tertiary health facility. RESULTS: From September 2004 to March 2006, 215 patients were studied. There was a female preponderance (p<0.01). Among patients over eighty, 72% had hypertension and atrial fibrillation was more common among the oldest old (p<0.01). CONCLUSION: Hypertension and atrial fibrillation should be treated aggressively in the elderly. Anticoagulants should be considered more often in these patients. INTRODUÇÃO: Acidente cerebrovascular (AVC) isquêmico é geralmente um evento catastrófico, particularmente em idosos. Envolvimento cardiovascular é a principal causa de AVC na população desta faixa etária; dessa forma, o conhecimento acerca de seus fatores de risco é importante para a definição de políticas específicas de prevenção. OBJETIVO: Avaliar a prevalência de fatores de risco cardiovasculares em pacientes com idade igual ou superior a 80 anos numa população hospitalar tendo AVC isquêmico. MÉTODO: Estudo retrospectivo de pacientes consecutivos diagnosticados como AVC admitidos em um centro de saúde terciário. RESULTADOS: De setembro de 2004 a março de 2006, 215 pacientes foram estudados. Houve predomínio do sexo feminino (p<0,01). Entre os pacientes com mais de 80 anos, 72% tinham hipertensão e fibrilação atrial foi mais comum entre os idosos em idade mais avançada (p<0,01). CONCLUSÃO: Hipertensão e fibrilação atrial devem ser tratados agressivamente em idosos. Anticoagulantes devem ser considerados mais freqüentemente nestes pacientes.